Kerja Sama Uni Eropa dan Libya Dalam Penanganan Perdagangan Manusia Terhadap Migran 2017-2020 - Syarifah, Shofy Ufairoh; Sidik, Hasan (Indonesia Center for Middle East Studies, 2022)
Libya is a transit country for migrants from the Sub-Saharan region, North Africa, and the Middle East, while Europe was the main destination for migrants and refugees. In 2016 a wave of migration occurred in Europe, especially from North Africa to Italy. Migration waves caused other problems, including human trafficking that occurred among migrants, so the European Union and Libya cooperate. This study aims to find out how cooperation between the European Union and Libya can deal with human trafficking in the period 2017-2020, as well as find out about the flow of migrants. To answer this, the author uses the concept of international cooperation and human rights used qualitative methods. In the process, the researcher conducted interviews with experts. From this research, it was found that both of them had a role. Several points of cooperation could be overcome, but they still could not be resolved in the case ofhuman trafficking